Effect of Si Content on Thermal Shock Resistance of Al-Si-Cu Alloys - F. Khomamizadeh; V. Firouzdor; S. Khoshkooei; E. Nejati; M. Akbari (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
In this study the effects of Si content on mechanical and thermal fatigue properties of Al-Si casting alloys were investigated. Repeated heating and cooling cycles were applied on the samples at 230°C to develop thermal fatigue cracks. Crack growth mechanisms and microstructural influences were investigated by optical and scanning electron microscopy. Thermal fatigue behaviors were improved successively by increasing of silicon content up to 7wt%. However, addition of more than 9wt% silicon decreased the thermal shock resistance of the alloy. Silicon contents of about 9wt% presented the best mechanical and thermal fatigue resistance in the alloy.